2019
DOI: 10.1177/0886260519864371
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Minority Stress and Intimate Partner Violence Among Homosexual Women in Turkey

Abstract: Intimate partner violence (IPV) has been recognized as an important public health problem over the past two decades, and increased attention to violence in intimate relationships has been given to heterosexual couples. Although the vast majority of literature has determined the rate of IPV among lesbian, gay, bisexual couples, and relationship quality, few studies investigated how stress specific to living as a lesbian or bisexual woman might correlate with IPV in these relationships. For this reason, the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
1
22
1
Order By: Relevance
“…In Turkey, whilst IPV has been studied more extensively, only one report examines IPV among LB. Ayhan-Balik and Bilgin (2019) found that all forms of IPV perpetration occurred among lesbians in Turkey, but the most prevalent type was psychological violence (66.4%). Keeping the limited studies on psychological IPV among LB in mind, our first aim in the current study was to investigate the prevalence rates of psychological IPV perpetration among LB in relation to sexual orientation and country.…”
Section: Prevalence Of Psychological Ipv Perpetration Among Lbmentioning
confidence: 99%
“…In Turkey, whilst IPV has been studied more extensively, only one report examines IPV among LB. Ayhan-Balik and Bilgin (2019) found that all forms of IPV perpetration occurred among lesbians in Turkey, but the most prevalent type was psychological violence (66.4%). Keeping the limited studies on psychological IPV among LB in mind, our first aim in the current study was to investigate the prevalence rates of psychological IPV perpetration among LB in relation to sexual orientation and country.…”
Section: Prevalence Of Psychological Ipv Perpetration Among Lbmentioning
confidence: 99%
“…In addition, the collective high school experiences expressed by the participants were also an outlier to the Turkish norm since this setting was one of the few specialized residential gifted schools in the nation where our participants had the luxury to be exposed to controversial social issues and experience intellectual debates. Of note, the participants in our study came from a relatively well-educated group, which does not correspond to the average level of education in Turkey (Ayhan Balik & Bilgin, 2019; Bakacak & Ōktem, 2014). Therefore, we encourage readers to interpret the results with these considerations in mind.…”
Section: Discussionmentioning
confidence: 96%
“…In Turkey, where the participants of the present study are originally from, prescribed gender roles, heterosexism, and a patriarchal culture prevail in society (Ayhan Balik & Bilgin, 2019; Bakacak & Ōktem, 2014; Kandiyoti, 2003). Despite the existence of LGBTQ+ activism and increasing exposure to LGBTQ+ matters via globalization and digital media, gender nonconformity is still considered taboo and invites physical and social hostility (Engin, 2015; Fishman, 2013; Gorkemli, 2012).…”
Section: Sexual Minorities and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations